Personal, social and organizational factors in usage of collaboration systems for research - Zakaria, Halimi; Mohd Daud, Norzaidi; Idris, Fazli (2012)
This paper attempts to investigate the relationship between personal, social and organizational factors with the usage of collaborative systems for research.The target population for this study is the academic staffs of Malaysia research universities. The personal related factors are personal innovativeness and task-technology-fitwhereas the social factors are subjective norm and peer acceptance.The organizational factors are training and management support.The relationship of these three perspectives (i.e. personal, social and organizational) in relation with usage of collaborative systems is studied using a model adapted from Technology-Organization-Environment (TOE) model and incorporating it with the Technology Acceptance Model (TAM).Data analysis presents the descriptive statistics of the respondents, the reliability and validity of the instruments used and correlational analysis of the factors.In conclusion, this paper proposes a framework incorporating these factors that are important in influencing usage of collaboration systems for academic research.